CLASSIFICATION OF THE MACHINE TECHNOLOGICAL SYSTEMS IN PLANT INDUSTRY - V. M. Beylis (Сельскохозяйственные машины и технологии)
The need of expansion of works on normalization and development of machine technologies system for transition to technologisation of agro-industrial production was defined. Relevance of systematization of the saved-up practical experience, scientific development and information, and also classifications of a great number of the interconnected technological objects was presented. The principles of systematization were established: from normalization of objects on a purely formal external sign till justification of creation of the systems based on objective laws. It was noted that systematization accumulates the studied objects in complete structural system on the basis of a number of simultaneously considered criterions. A number of classification problems was solved due to mathematical methods (mathematical statistics, cluster, factorial, dispersive analysis). It was defined that classification of technical means is based on rules of separation of concerns and abidance of the basic principles of the ordered creation of system of studied multitude data. It was established that it is especially importance to choose correctly the essential criterion of classification giving the chance educing of qualitative differences between grades. An orienting point is first of all the technological mission of the mechanism or a technical mean defining their qualitative and quantitative characteristics. It was proved out that the technology in a general sense is the concrete, intended by the consumer way to achievement of the specify goal of useful activity. It was established that agricultural technologies belong to the category of «flexible». In real production conditions there are not constant technology, because choice of it directly depends on random factors and the person making decisions. It was drawn the conclusion that carrying out this work creates potential possibility of justification of the not known earlier directions of development of scientific and technical progress by identification of not studied types of objects of classification.